Chromatographic and Spectrophotometric Evaluation of Progesterone and Estrogen - Aniket Kumar and Manoj G. Tyagi*, Sangeetha C. Jambu, Sowmya Vilvan (Recent Research in Science and Technology, 2010)
Steroid hormones viz. progesterone, estrogen were estimated through TLC in a concentration and time dependent manner i.e. 2.5mg/ml, 5.0mg/ml for 30 & 45 minutes and, 0.2mg/ml, 0.4mg/ml for 30 & 45 minutes respectively. Progesterone and estrogen were stained with 50% v/v aq. solution of Conc. H2SO4 and were estimated through TLC in a concentration and time dependent manner. Different steroid hormones travel at different rates due to the differences in their attraction to the stationary phase and because of differences in solubility in the solvent. These Rf values obtained from both the hormones were then compared and it was found that there was a reasonable difference. Further, a study on the interaction of steroid hormones with fatty acids and proteins was undertaken using a spectrophotometer. Steroid hormones viz. progesterone and estrogen were made to interact with measured amounts of alcohol, stearic acid and bovine serum albumin (BSA) and their absorbance were recorded at the excitation wavelength of 410 nm using a spectrophotometer. Progesterone (conc.2mg/ml) and estrogen (conc. 0.5mg/ml) were each mixed with 0.1 ml, 0.2ml and 0.4ml of stearic acid (conc. 0.5mg/ml) and 5 mg, 10 mg and 15 mg of BSA separately and their absorbance were noted at 410nm. A slight shift in the absorbance was found on the overall interaction of steroids: progesterone and estrogen with alcohol, stearic acid and BSA respectively, when excited to 410 nm. Thus an attempt was made to establish a valid spectrophotometric procedure for the study of interaction of steroid hormones with fatty acids and proteins.